Risk of childhood psychiatric disorders in children of refugee parents with post-traumatic stress disorder: a nationwide, register-based, cohort study - Maj Back Nielsen, MS; Jessica Carlsson, MD; Martin Køster Rimvall, MD; Jørgen Holm Petersen, PhD; Marie Norredam, DMSc (Elsevier, 2019)
Summary: Background: Children of refugees are often exposed to the consequences of parental post-traumatic stress disorder (PTSD), potentially leaving them vulnerable to intergenerational transmission of psychopathology. The present study aimed to determine whether parental PTSD is associated with childhood psychiatric morbidity among children of refugees. Methods: This study is a two-generation nationwide cohort study using the Danish Immigration Services database. We followed up children younger than 18 years with at least one refugee parent until psychiatric contact, end of the study, their 18th birthday, emigration, or death. We excluded children if their parents were diagnosed only with psychiatric diagnoses other than PTSD or if they had received a psychiatric contact before parental PTSD diagnosis. Information on parental PTSD and offspring psychiatric morbidity was obtained from the Danish Psychiatric Central Research Register. We used Cox proportional hazards regression models to assess the risk of psychiatric contacts among children of refugees with PTSD compared with children of refugees with no psychiatric diagnosis. Findings: Between Jan 1, 1995, and Dec 31, 2015, 102 010 refugees obtained residency permission in Denmark and 62 239 biological children of refugees were born in Denmark before Dec 31, 2015. 51 793 were eligible and included in the study (median follow-up 7·15 years [IQR 3·37-11·78]); of these, 1307 (2·5%) children had a psychiatric contact. 7486 (14·5%) children of refugees were exposed to parental PTSD. Parental PTSD significantly increased the risk of psychiatric contact in offspring (hazard ratio 1·49 [95% CI 1·17-1·89] for paternal PTSD, p=0·0011; 1·55 [1·20-2·01] for maternal PTSD, p=0·00084) after adjustment for sociodemographic variables. Interpretation: Children of refugees exposed to parental PTSD are at increased risk of psychiatric morbidity. Targeted screening and interventions are necessary to prevent psychiatric morbidity and ensure access to adequate care. Funding: Section for Immigrant Medicine, Department of Infectious Diseases, Copenhagen University Hospital Hvidovre.